Schutz von Sanierungsfinanzierungen in Liquidationsverfahren Ein deutsch-französischer Rechtsvergleich - Locher, Johannes (Mohr Siebeck, 2023)
New credit is typically of paramount importance for any restructuring attempt. However, if such an attempt fails, all stakeholders stand to face considerable disadvantages. Johannes Locher examines how lenders are protected against these risks in German and French law and analyses whether the protection afforded in Germany could be extended along the lines of French law.
PublicationDate: 20231206
Keywords: Insolvenzrecht -- Kreditsicherung -- Sanierungsrecht -- Verfahrensziele -- Eheschließung -- Bürgerliches Recht -- Zivilverfahrensrecht, Insolvenzrecht -- Ausländisches Recht, Rechtsvergleichung